PENGEMBANGAN ALAT EKSPERIMEN TEORI KINETIK GAS SEBAGAI MEDIA PEMBEJARAN FISIKA DI SMA - Ridwan Ramadhan; Zulhelmi '; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to test the validity of the experimental devices kinetic theory of gases consisting of experimental tools and the escort book of experiment tools. The approach used in this study is the development of research (Research Development) by using the 4D model (Four D Models).  The data obtained from the assessment given by the validator. Validator consists of  3 lecture of physics education departemen faculty teacher training and education of Riau university and 2 senior high school physics teacher.  The data were analyzed by descriptive analysis. Based on data analysis of tools experimental kinetic theory of gas validation  are at very high category with a score of 3.75 and the validation escort book of experiment tools are at very high category with a score of 3.54. The results of this study is indicate that the experimental kinetic theory device is a valid used as  learning physics media at school. Key Words: Validation, the experimental device, Model 4D